Internet Gaming Disorder of Gamers: A Study on Values and Online Gaming Behavior - Jessica Angelina Ongkowijaya; Esther Widhi Andangsari (Engineering Proceedings)
This research aims to explore the effect of Internet Gaming Disorder (IGD) and online gaming behaviors related to IGD. The explored behaviors were based on games with microtransactions. Using a revised portrait value questionnaire (PVQ-RR), 186 respondents from 18 to 52 years old were asked about gaming behaviors. Online gaming behaviors such as the duration of online gaming and the payment for online games had a reciprocal relationship with IGD. Stimulation, achievement, hedonism, power through dominance, and personal security were correlated with playing paid online games. It is necessary to consider the fact that the values of the games are related to online gaming behaviors. Positive online gaming behaviors need to be developed.